(The 3rd ICBESS 2016 - PROCEEDING Kartika Discovery Hotel Bali, August 10 – 11, 2016) ENTREPRENEUR ORIENTATION IN ISLAMIC PERSPECTIVE - Dedeng Abdul Gani Amruloh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
Islam for his people understood as a way of life, Islam is a complete and comprehensive religion, guide to the various aspects of practicing a profession set out in the main pillars of Islam, the Qur'an and the Hadith, including how a Moslem life as an entrepreneur. Islam is a religion of entrepreneurship, it is characterized by the verses of the Qur'an and the Sunnah of the Prophet Muhammad that enables and encourages entrepreneurial activity, such as use of the opportunities, take risks and innovative. Islam has a broader perspective on entrepreneurial success, the meaning of success as mentioned in Al-Qur’an associated with falaha, aflaha and word said faza fauzan. Formula of succes is : halal, qonaah, taufiq, saadah and Jannah. This article is about how the perspective of Islam based on the Qur'an and the Sunnah of Rasulullah SAW to entrepreneurial orientation. The Purpose of this paper is to develop a model of entrepreneurial orientation in Islamic prespective. The study is descriptive, and the nature of the paper is conceptual, the study draws on secondary materials through library research. In the paper entrepreneurship and entrepreneur orientation models are develop by Islamic Prespective. The model would be used for developing entrepreneurial orientation with Islamic prespective for other study or researh in entrepreneurship science and practices. Keywords: Islamic, Entrepreneuship, Entrepreneurial Orientation, Moslem Entrepreneur, Islamic prespective